Diffuse Esophageal Leiomyomatosis and the Surgical Challenges Encountered - Tanvi Luthra; Sachit Anand; Anjan Kumar Dhua; Devendra Yadav; Vishesh Jain; Prabudh Goel; Devasenathipathy Kandasamy; Sandeep Agarwala; Rohan Malik (Wolters Kluwer Medknow Publications, 2024)
Diffuse esophageal leiomyomatosis (DEL) is a rare condition characterized by the growth of multiple benign smooth muscle tumors (leiomyomas) in the esophagus. These tumors can cause obstruction and functional impairment of the esophagus, leading to symptoms such as difficulty swallowing, chest pain, and weight loss. The disease can present with leiomyomas or glomerular nephropathy in other body parts, hearing defects, astigmatism, or myopia (Alport's syndrome). However, isolated cases are also reported in the literature. Surgical management of DEL presents several challenges due to the location and extent of the tumors. Herein, we describe a girl afflicted with DEL and required multiple surgeries for management, highlighting the unique challenges faced by the surgical team in restoring esophageal function and improving the patient's quality of life.